Water deprivation induces biochemical changes without reduction in the insecticidal activity of maize and soybean transgenic plants - Silva, Juliana Barroso [UNESP] (2021)
Like conventional crops, transgenic plants expressing insecticidal toxins from Bacillus thuringiensis (Bt) are subjected to water deprivation. However, the effects of water deprivation over the insecticidal activity of Bt plants are not well understood. We submitted Bt maize and Bt soybean to water deprivation and evaluated biochemical stress markers and the insecticidal activity of plants against target insects. Bt maize (DAS-Ø15Ø7-1 × MON-89Ø34-3 × MON-ØØ6Ø3-6 × SYN-IR162-4) containing the PowerCore Ultra traits, Bt soybean (DAS-444Ø6-6 × DAS-81419-2) with the Conkesta E3 traits, and commercial non-Bt cultivars were cultivated and exposed to water deprivation in the greenhouse. Leaves were harvested for quantification of hydrogen peroxide, malondialdeyde (MDA), and total phenolics and insecticidal activity. Maize or soybean leaf disks were used to evaluate the insecticidal activity against, respectively, Spodoptera frugiperda (J.E Smith) and Chrysodeixis includens (Walker) neonates. Except for Bt soybean, water deprivation increased hydrogen peroxide and MDA contents in Bt and non-Bt plants. Both biochemical markers of water deficit were observed in lower concentrations in Bt plants than in non-Bt commercial cultivars. Water deprivation did not result in changes of phenolic contents in Bt and non-Bt maize. For Bt or non-Bt soybean, phenolic contents were similar despite plants being exposed or not to water deprivation. Water deprivation did not alter substantially insect survival in non-Bt maize or non-Bt soybean. Despite water deprivation-induced biochemical changes in plants, both Bt plants maintained their insecticidal activity (100% mortality) against the target species.